Konsep Dasar Supervisi Dalam Bimbingan dan Konseling Pola 17 Plus - Defri Yenita; Dasril Dasril (Jurnal Pendidikan dan Konseling (JPDK), 2022)
The purpose of this writing is to find out the basic concept of guidance and counseling pattern 17 plus which is that guidance is centered on the individual self, based on the abilities and needs of the individual so that he is able to overcome himself and develop all the abilities he has. So Guidance Counseling provides consulting services which are a type of service from the pattern 17 system. Consulting services and mediation services are services resulting from the development of the pattern 17 system. At this time pattern 17 has experienced significant developments based on the conditions in the field. Now pattern 17 has changed to pattern 17 plus in which there are several additional services that are useful for students and the community in the school environment. BK supervision to increase the professionalism of BK teachers explained how to improve the professionalism of guidance and counseling, supervision and guidance from the principal as a supervisor is needed. The professionalism of counseling teachers and the role of counseling supervision in increasing the professionalism of counseling teachers aims to describe the professionalism of counseling teachers and the role of counseling supervision in increasing the professionalism of counseling teachers. In the application of counseling it is necessary to master skills and personality development. Counseling services for the Counseling Guidance Teacher profession are services that must be mastered properly